Pemanfaatan Kecerdasan Buatan di Era Digital: Analisis Dampak, Tantangan, dan Implikasi terhadap Regulasi Hukum di Indonesia - Rohaini .; Melisa; Nabila Gusriyanti; Aldo Felyo; Lilis Amelia; Muh Raditya Caesare (CV. ITTC INDONESIA, 2025)
The development of digital technology, particularly Artificial Intelligence (AI), has significantly transformed various aspects of human life, including the legal system. The implementation of AI in the legal sector in Indonesia offers efficiency, accuracy, and accessibility of legal services but also poses complex legal, ethical, and regulatory challenges. This study employs a normative qualitative approach with a case study design to analyze AI utilization in legal practice, evaluating its impact, challenges, and implications for national regulation. The findings indicate that while AI can assist in legal data analysis, case prediction, and digital legal consultation, regulatory gaps exist concerning accountability, privacy risks, algorithmic bias, and limited human resource capacity. This study emphasizes the urgency of adaptive legal reform, the establishment of ethical AI guidelines, and enhancing digital literacy among legal practitioners to ensure responsible and equitable utilization of technology